Loan supply, credit markets and the euro area financial crisis - Carlo Altavilla; Matthieu Darracq Pariès; Giulio Nicoletti (European Central Bank (ECB), 2015)
We use bank-level information on lending practices from the euro area Bank Lending Survey to construct a new indicator of loans' supply tightening controlling for both macroeconomic and bank-specific factors. Embedding this information as external instrument in a Bayesian vector autoregressive model (BVAR), we find that tighter bank loan supply to non-financial corporations leads to a protracted contraction in credit volumes and higher bank lending spreads. This fosters firms' incentives to substitute bank loans with market finance, producing a significant increase in debt securities issuance and higher bond spreads. We also show that loans' tightening shocks explain a large fraction of the contraction in real activity and the widening of credit spreads especially over the recession which followed the euro area sovereign debt crisis.
Keywords: E51; E44; C32; 330; Bank Lending Survey; Credit Supply; External Instruments; Lending standards